INTERESTING MOON’S SURFACE FEATURES. OUR STUDY AND SOME INFERENCES - Bondarenko, Yu. N. (Одеські астрономічні публікації, 2013)
In this article the results of the long-term CCD observations of the Moon are presented. We describe some unusual features existing on the Moon’s surface and discuss their possible origin.